Validitas dan Praktikalitas Rencana Pembelajaran Semester (RPS) Terintegrasi Research Based Learning - Umil Muhsinin; Kiki Fatmawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
The research results show that most students find it difficult to complete their studies. One reason is the lack of ability to write scientific papers, the weakness of research methodology and the lack of student involvement in lecturer research. Therefore, research on the development of integrated semester learning plans is based on research. This research aims to produce a valid and practical RPS. The model used in this development is the 4-D model. The study was conducted in Semester V, majoring in PGMI FTK UIN STS Jambi. Data collection techniques used a questionnaire consisting of an expert validation sheet, a lecturer response sheet to the RPS, and a RPS implementation sheet. The results showed that the learning tools developed had met the valid and practical criteria. This can be seen based on the results of the validation of the RPS by expert validators and education practitioners who have been implemented, which developed an average score of 3.9 with a very valid category. The practicality of RPS is known from observations of the implementation of learning with an average of 93.3% the category is very practical, the questionnaire responses of lecturers on average is 90% with the practical category.